2008
DOI: 10.1111/j.1601-5223.1985.tb00468.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro growth kinetics of mouse trisomies 12 and 19

Abstract: Hypoplasia and retardation of the fetus are prominent developmental features in trisomies of the mouse. They are caused by disturbances and depression of growth in vivo. In a study of growth parameters of two trisomic mice. Ts12 and Ts19, cell cultures were initiated from Ts12, Ts19 and normal embryos at late developmental stages. Kinetics of growth of these cells under different conditions show that growth is not significantly affected in either of the trisomies. These results indicate that the trisomy‐depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…S6) was increased in trisomic cell lines. Cell proliferation was also impaired in primary cells from humans with Down Syndrome (Trisomy 21) but a specific cell cycle defect was not observed either (15,16). It is possible that progression through the cell cycle is slowed overall in trisomic mouse and human cells.…”
Section: Cell Volume Is Increased In Trisomic Cellsmentioning
confidence: 99%
“…S6) was increased in trisomic cell lines. Cell proliferation was also impaired in primary cells from humans with Down Syndrome (Trisomy 21) but a specific cell cycle defect was not observed either (15,16). It is possible that progression through the cell cycle is slowed overall in trisomic mouse and human cells.…”
Section: Cell Volume Is Increased In Trisomic Cellsmentioning
confidence: 99%
“…Postzygotic reproductive barriers concern all the events that occur after fertilization, such as reduced hybrid viability and fertility, while prezygotic reproductive barriers concern isolation of sexual partners via ecological, temporal or behavioral isolation. Pheromones play a key role in pre-mating recognition of sexual partners [2]. These compounds are defined as substances released by an animal that are able to induce specific behavioral and/or endocrinological reactions in a sexual partner of the same species [3].…”
Section: Introductionmentioning
confidence: 99%
“…Of course, the prolonged cell cycle, selective disadvantage and fetal growth retardation could merely be nonspecific effects of chromosomal imbalance (Mittwoch 1971). However, while some authors have demonstrated a prolonged rate of cellular proliferation in human fibroblast (Kaback & Bernstein 1970, Schneider & Epstein 1972, Segal & McCoy 1973, Cure et al 1974, Paton et al 1974 and murine (Hongell 1981, Hongell & Gropp 1982 autosomal trisomies, others have found either no significant difference in trisomic human fibroblasts (Kukharenko et al 1974, Hoehn et al 1980, Kajii et al 1980, Hassold & Sandison 1983, trisomic human lymphocytes (Crossen & Morgan 1980, Frias & Carnevale 1983 and murine trisomies (Gropp 1982, Nielsen et al 1985, or even a decrease in cell cycle time of cells with trisomy 21 (Heidemann et al 1983). In addition, seventy of effect on the mitotic cycle has not correlated with amount of additional or missing chromatin (Epstein 1986).…”
Section: Discussionmentioning
confidence: 98%